Role Of Egg Surface Alkaloids In Cannibalism And Intraguild Predation In Two Species Of Aphidophagous Ladybird Beetles (Coleoptera: Coccinellidae) - NAVODITA GEORGE MAURICE; ANOORAG R. TAYDE (International Journal of Pharma and Bio Sciences, 2012)
Cannibalism and intraguild predation (IGP) are two very imperative constituents determining the structure of biological communities. Ladybird beetles, frequently known as the farmer’s friends, easily partake in cannibalism and IGP when their usual prey i.e., aphid population declines. Eggs although defenseless, fall easy victim both for the adults as well as the larvae of the ladybirds and are demolished thus, providing a chance to endure life. The eggs are encrusted with alkaloids helping in easy recognition of conspecific as well as heterospecific eggs. A study was conducted to identify the role of these alkaloids in cannibalism and intraguild predation among two aphidophagous ladybird species namely, Cheilomenes sexmaculata and Coccinella transversalis. Results specify that the fourth instar and adult female of C. sexmaculata have a strapping propensity to chip in intraguild predation while C. transversalis favours cannibalism.